1983
DOI: 10.1001/archderm.119.2.117
|View full text |Cite
|
Sign up to set email alerts
|

Psoriasis therapy. The effect of UV radiation on sensitization to mechlorethamine

Abstract: A study was performed to determine the effect of UV-B radiation on the sensitization of patients to topically applied mechlorethamine hydrochloride. Patients with widespread psoriasis were randomized into two groups. One group was given six daily treatments of one minimal erythemal dose (MErD) prior to starting daily applications of a 0.02% mechlorethamine ointment and, thereafter, one MErD weekly; the other group was given daily applications of mechlorethamine but received no UV-B. The improvement of psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Of the 23 patients with CIM in our study, CIM occurred within the first month of treatment with mechlorethamine in 13 (56%) and within 3 months in 21 (91%). These data are similar to that of previous reports 6,7,9,11,19 that CIM usually occurs in the first weeks of mechlorethamine treatment.…”
Section: Commentsupporting
confidence: 92%
See 1 more Smart Citation
“…Of the 23 patients with CIM in our study, CIM occurred within the first month of treatment with mechlorethamine in 13 (56%) and within 3 months in 21 (91%). These data are similar to that of previous reports 6,7,9,11,19 that CIM usually occurs in the first weeks of mechlorethamine treatment.…”
Section: Commentsupporting
confidence: 92%
“…In patients with psoriasis, it has been shown that intravenous desensitization to mechlorethamine is unsuccessful. 10 Therapy with UV-A or UV-B can reduce the incidence of allergic contact dermatitis caused by mechlorethamine therapy 11 and delays contact sensitization to mechlorethamine. 12 In patients with MF, there is no clear evidence that the use of PUVA therapy delays the development of mechlorethamine sensitization.…”
Section: Commentmentioning
confidence: 99%
“…With respect to the prevention of allergic dermatitis to mechlorethamine, we obtained similar results with PUVA to those of Nusbaum et al (1983) with UV-B. We did not find the combination of PUVA and mechlorethamine more efficient than PUVA alone in clearing psoriasis (Ortonne et al, 1977).…”
Section: Discussionmentioning
confidence: 56%
“…In this study patients were not randomized, varying doses of UV were given before starting mechlorethamine and UV therapy was discontinued at varying intervals after commencing mechlorethamine. Nusbaum et al (1983) studied 20 psoriatic patients randomized into two groups. In one group G.Mauduit, O.Silvestre and J.Thivolet mechlorethamine ointment was used alone and in another group patients were treated with mechlorethamine daily after six UV-B treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation